Biogas Tinja Manusia dalam Perspektif Fiqih-Kimia - Ummi Khoiriyah, Wawan Juandi Muhyiddin Khatib (ISLAMICA: Jurnal Studi Keislaman, 2012)
Energy is one of the most important factors to global prosperity. The dependence on fossil fuels as primary energy source has led to global climate change, environmental degradation, and human health problems. In order to reduce dependence on commercial energy, steps have been taken to develop an alternative source, such as biogas. Biogas was a gas produced from biological activities in anaerobic fermentation processes and as a renewable energy. Biogas is one form of the alternative energy. It is environmentally friendly. However, biogas and its utilization still pose a serious problem within Muslim community, especially the pesantren. It is not easy for the pesantren to accept it on jurisprudential grounds. This paper attempts to examine the nature of biogas by looking at it as a human waste, and how does Islamic jurisprudence (fiqh) treat human waste particularly in terms of its use for human purpose. The paper also compares fiqh perspective with that of chemistry. The underlining argument that the paper tries to build is that legal compound component of human waste biogas (methane, carbon dioxide, hydrogen sulfide) is sacred, and must therefore be treated accordingly